(3Pjd GdYbO GdePgH aj WHbGJ GdePgH (B( (3ePgH GdEeGe eMeO GdTGaYi (B)s - (3SQGL GdOjf CHh MaU YeQ Hf CHi GdMSf Ydj GdfMhi Hf CMeO Hf eMeO GdCfUGQj GdCfOdSj GdeQSi GdeYQha HGHf Gdebdfs; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3QHfG BJfG ef dOfc QMeI hgF dfG ef CeQfG QTOG hHYO agPG Pjd Ydi WHbGJ GdabgGA Ydi MQha GdeYLe dG Ydi GdSfjf s
(3BNQgG (B:s
(3bGd eDdag BNQ eG CYGf Gddg Ydi EdMGbI hddg GdMeO Je GdPjd Ydi WHbGJ GdTGaYjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JPjjds
Keywords: (3GdJGQjNs